Circadian Features of Neutrophil Biology - Aroca-Crevillén, Alejandra; Adrover, José M.; Hidalgo, Andrés (Frontiers in Immunology, 2020)
Rhythms in immunity manifest in multiple ways, but perhaps most prominently by the recurrent onset of inflammation at specific times of day. These patterns are of importance to understand human disease and are caused, in many cases, by the action of neutrophils, a myeloid leukocyte with striking circadian features. The neutrophil’s short life, marked diurnal variations in number, and changes in phenotype while in the circulation, help explain the temporal features of inflammatory disease but also uncover core features of neutrophil physiology. Here, we summarize well-established concepts and introduce recent discoveries in the biology of these cells as they relate to circadian rhythms. We highlight that although the circadian features of neutrophils are better known and relevant to understand disease, they may also influence important aspects of organ function even in the steady-state. Finally, we discuss the possibility of targeting these temporal features of neutrophils for therapeutic benefit.